Aktivitas Fisik Rutin sebagai Anti-Aging dan Pencegahan Sarkopenia pada Wanita: Tinjauan Pustaka - Dewi, Ade Yasinta; Ayu Dewi, Ni Nyoman (PT Kalbe Farma Tbk., 2026)
Aging is a natural process of declining body functions, including a decrease in muscle mass and strength known as sarcopenia. Sarcopenia has a higher prevalence in menopausal women due to the decline in estrogen levels. This condition affects quality of life, fall risk, and independence. This literature review explores the role of regular physical activity as an anti-aging intervention and prevention of sarcopenia in women. A literature search was conducted in the Google Scholar, PubMed, ScienceDirect, and DOAJ databases for relevant articles (originalresearch or reviews) published between 2024 and 2025. Data analysis used a narrative synthesis approach on 30 selected articles. Results showed that consistently performed physical activity, especially resistance training (moderate–high intensity), multimodal training, andtraining with blood flow restriction, is highly effective in improving muscle mass, strength, and physical function. Combination of physical activity with adequate protein intake (≥ 1.0 g/kgBB/day) showed significant synergistic effects, especially in women with sarcopenic obesity.Technology-based interventions potentially improve program adherence. It is concluded that regular physical activity, particularly resistance training supported by optimal nutrition, is an effective non-pharmacological strategy to slow the aging process and prevent sarcopenia.